Nationalism, Transnationalism, and Political Islam Hizbullah's Institutional Identity - Hage Ali, Mohanad (Springer International Publishing, 2018)
This book sheds light on how Hizbullah has transformed religious rituals and supernatural narratives in order to mobilize the Shi'a community. The author examines how Hizbullah has altered its institutional structure and reconstructed Lebanese Shi'a history in a manner similar to that of nationalist movements. Through fieldwork and research, the project finds that Hizbullah has centralized around the concept of Wilayat al-Fagih (Gaurdianship of the Islamic Jurists): in essence, the absolute authority of Iran's Supreme Leader over the Shi'a "nation.".